2021
DOI: 10.3847/1538-4357/abfaf6
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic Star Formation History Measured at 1.4 GHz

Abstract: We matched the 1.4 GHz local luminosity functions of star-forming galaxies (SFGs) and active galactic nuclei to the 1.4 GHz differential source counts from 0.25 μJy to 25 Jy using combinations of luminosity and density evolution. We present the most robust and complete local far-infrared (FIR)/radio luminosity correlation to date in a volume-limited sample of ≈4.3 × 103 nearby SFGs, finding that it is very tight but distinctly sublinear: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 45 publications
5
45
1
Order By: Relevance
“…We examined SFRD evaluated from constant radio to IR luminosity fraction for all redshift and found that constant 𝑞 TIR gives higher SFRD at 𝑧 > 3.5. Matthews et al (2021) introduced luminosity dependent non-linear 𝑞 parameter in order to exclude the bias caused by flux limited sample. The FIR/radio correlation is a critical quantity to draw SFRD from radio luminosity.…”
Section: Discussionmentioning
confidence: 99%
“…We examined SFRD evaluated from constant radio to IR luminosity fraction for all redshift and found that constant 𝑞 TIR gives higher SFRD at 𝑧 > 3.5. Matthews et al (2021) introduced luminosity dependent non-linear 𝑞 parameter in order to exclude the bias caused by flux limited sample. The FIR/radio correlation is a critical quantity to draw SFRD from radio luminosity.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, we also plot the cosmic star formation rate density (SFRD) from Madau & Dickinson (2014), Zavala et al (2021) and the radio-derived SFRD from Matthews et al (2021) in Fig. 14.…”
Section: Comparing the Agn Luminosity Density With The Sfrdmentioning
confidence: 99%
“…We include comparisons of the luminosity density from previous results(Ranalli et al 2016;Lacy et al 2007) as shown in the upper left legend. Additionally shown on the right side y-axis (and the lower right legend) are the star formation rate densities (SFRD) fromMadau & Dickinson (2014),Zavala et al (2021), and the 1.4 GHz radio-derived SFRD fromMatthews et al (2021).…”
mentioning
confidence: 99%
“…Though there have been many attempts to explore its evolution, it remains still controversial (e.g., Bourne et al 2011;Mao et al 2011;Schleicher & Beck 2013;Schober et al 2016;Delvecchio et al 2021;Molnár et al 2021). In spite of such uncertainties, the potential use of the radio continuum as an SFR estimator has attracted attention (e,g., Bell 2003;Murphy et al 2011;Matthews et al 2021). Particularly, the recent development of long-wavelength facilities is a driving force to push forward such studies, gearing at the SKA (e.g., Shao et al 2018;Read et al 2018;Tisanić et al 2022).…”
Section: Introductionmentioning
confidence: 99%